COMMUNITY-BASED NATURAL DISASTER PREPAREDNESS EDUCATION IN DIMPONG VILLAGE, NORTH RAHONG DISTRICT IN AN EFFORT TO REDUCE DISASTER RISK - Krowa, Yuliana Reginaldis Rosali; Meku, Fransiskus Xaverius; Beo, Yosef Andrian; Eka, Angelina Roida (LPPM Univ. Ibn Khaldun Bogor, 2024)
Every year Indonesia has the potential to experience various natural disasters that have an impact on human life, depending on its geographical location and natural structure, as well as climate change which also contributes to an increase in the incidence of natural disasters. The various natural disasters that hit Indonesia require people to be ready, responsive and alert to disasters. The community is a key element in dealing with disasters, apart from being the first to know about disaster events, the community is also the biggest victim in disasters, and is the source of disaster management. In general, Indonesian people are less prepared to face natural disasters due to a lack of knowledge in preparing themselves for disasters. The community in Dimpong Village, Manggarai Regency has insufficient knowledge regarding pre-disaster preparedness, especially natural disasters. This can be handled by providing information about pre-disaster preparedness and carrying out analyzes related to disaster risk reduction, including identifying dangerous conditions for the area, vulnerabilities in the community, and available capacity in the community. This disaster risk reduction effort is an assessment in implementing a new paradigm in disaster management in Indonesia. By providing education about pre-disaster preparedness, community knowledge increases in efforts to reduce disaster risk in their area.